The Man Who Stayed Behind - Rittenberg, Sidney; Bennett, Amanda (Duke University Press, 2001)
The Man Who Stayed Behind is the remarkable account of Sidney Rittenberg, an American who was sent to China by the U.S. military in the 1940s. A student activist and labor organizer who was fluent in Chinese, Rittenberg became caught up in the turbulence that engulfed China and remained there until the late 1970s. Even with access to China's highest leaders as an American communist, however, he was twice imprisoned for a total of sixteen years.Both a memoir and a documentary history of the Chinese revolution from 1949 through the Cultural Revolution, The Man Who Stayed Behind provides a human perspective on China's efforts to build a new society. Critical of both his own mistakes and those of the Communist leadership, Rittenberg nevertheless gives an even-handed account of a country that is now free of internal war for the first time in a hundred years
Description based on online resource; title from PDF title page (publisher's Web site, viewed 12. Dez 2020)
Keywords: BIOGRAPHY & AUTOBIOGRAPHY / Historical; Communists -- China -- History -- Biography